Legitimacy Ethnographic and Theoretical Insights - Pardo, Italo; Prato, Giuliana B. (Palgrave Studies in Urban Anthropology, 2019)
Global in scope, this original and thought-provoking collection applies new theory on legitimacy and legitimation to urban life. An informed reflection on this comparatively new topic in anthropology in relation to morality, action, law, politics and governance is both timely and innovative, especially as worldwide discontent among ordinary people grows. The ethnographically-based analyses offered here range from banking to neighbourhoods, from poverty to political action at the grassroots. They recognize the growing gap between the rulers and the ruled with particular attention to the morality of what is right as opposed to what is legal. This book is a unique contribution to social theory, fostering discussion across the many boundaries of anthropological and sociological studies.